Physical fitness in school children living in a low socio-economic area of Accra, Ghana - Lawerteh, Stella Elikplim (Department of Health and Rehabilitation Sciences, 2022)
Background Physical fitness is an important indicator of health in childhood and a strong predictor of wellbeing in later life. Adiposity, decreased aerobic fitness and low levels of physical activity (PA) are associated with cardiovascular disease risk in children (Andersen et al., 2004). Estimates of PA and fitness in young children at the population level is still lacking for many African countries such as Ghana. One major challenge to conducting research on PA and fitness in children in these settings is the lack of accurate and reliable measures of these constructs. Several valid and reliable field-based physical fitness tests require test kits that are too expensive for people working in low socio-economic settings and lack norms for this population (Smits-Engelsman et al., 2020a). The Alpha-fit is one of the most used tests in Europe (Cvejić et al., 2013; Kolimechkov et al., 2019; Ruiz et al., 2011) and is considered to be a valid, reliable, feasible and safe health-related fitness test battery (Assessing Levels of Physical Activity (ALPHA), 2009; Ruiz et al., 2011). However, the Alpha-fit does not assess movement skills (e.g. throwing and catching, hopping, and balance), and has no norms for children living in Sub Saharan Africa. In recognition of these challenges, the Performance and Fitness (PERF-FIT) test battery was developed to provide a set of valid, reliable fieldbased motor performance items for the assessment of health-related physical fitness in low resource communities (Smits-Engelsman, 2018). However, the validity of the PERF-FIT has not been examined in children within the Ghanaian context. The aims of this study were to determine: (1) the physical fitness levels of school children aged 6 to 12 years in a lowincome urban area in Ghana using the Alpha-fit and (2) the construct validity of the PERFFIT among school children aged 6 to 12 years in a low-income urban area in Ghana by comparing it to tests of the Alpha-fit which measure similar constructs. Method A cross-sectional study design was adopted. Three public elementary schools located in La, a suburb of the La Dade Kotopon Municipal Assembly (LADMA), Accra, Ghana which met the criteria of low socio-economic status, (on the basis of geographical location) was selected using convenience sampling. The total number of pupils aged 6 - 12 years in all three schools were 376. A total of 186 children (aged 6-12 years) took part in the study. Children who provided assent after their parents had consented to participate in the study were recruited. Prior to testing, demographic information, health status and PA levels of children provided by a researcher-developed parent questionnaire were documented. Children with physical or medical conditions [determined with the Children‟s Physical Activity Readiness Questionnaire] that would have made testing unsafe were excluded. The two-item Physical Activity Questionnaire (Prochaska et al., 2001) was used to measure participants‟ PA and to identify those meeting the World Health Organization (WHO) PA guidelines for children. Testing was done on a playground/designated classroom at the participants‟ school during Physical Education periods. Weight and height measurements were taken using an electronic weighing scale and a wall-mounted tape measure. Cardiorespiratory endurance, power, agility and motor skills performance were assessed using the PERF-FIT and Alpha-fit assessment batteries. Only the 20-meter shuttle run test (20mSRT), long jump, Body Mass Index (BMI), waist circumference and 4 x10 meter shuttle run (4 x10m SR) which are items 1, 3, 4, 5 and 7 respectively of Alpha-fit were assessed. The tests were carried out in accordance with the instruction manuals. In describing the fitness levels of the participants, the Alpha-fit norms were used (Kolimechkov et al., 2019), and scores for each component were categorized into very poor (below 3rd percentile), below mean (between 3rd and 25th percentile), normal range (between 25th to 75th percentile), above mean (between 75th and 97th percentile) and very good (above 97th percentile). For the PERF-FIT, scores were collated as raw scores. Descriptive statistics: mean, median, standard deviation, percentages, and frequencies were used to summarize descriptive data. To compare differences of scores on the PERF-FIT and Alpha-fit between those who meet the WHO recommended guidelines and those who did not, the Mann-Whitney U test was used. To test the construct validity, hypotheses were formulated and tested for the expected magnitude of the relation between scores on the PERF-FIT and Alpha-fit intended to measure partly comparable constructs. The level of significance used was 0.05 Results One hundred and eighty-six children (96 boys and 90 girls) from low-income homes participated in this study. The median age of participants was 10.00 years. Only 12% of fathers and 3% of mothers had tertiary education whereas 40% of fathers were Artisans and self-employed, 68% of mothers were traders. Participants who were found to have met the WHO recommendation for moderate-tovigorous physical activity (MVPA) were 65.6% (n = 120),only 15.6% (n = 29) participate in sports outside school. Majority of them, 86.6% (n= 161) walk to school and 28.5% (n = 53) were underweight. Categorizing the Alpha-fit items scores, for item 1(20mSRT), 72 % (n = 134) were below the mean, 1.3 % (n = 3) performed very poorly, 25.3 % (n = 47) had normal scores, only 0.5 % (n=1) scored above mean. For item 3 (long jump), 2.2 % (n = 4) scored very good, 23.7% (n = 44) were above the mean, 59.7% (n = 111) scored normal, 12.9% (n = 24) scored below the mean and 1.1% (n = 2) performed very poorly. For item 7 (4 x10m SR), 22.6% (n = 42) scored very good, 33.2% (n = 50), scored above the mean, 30.1 % (n = 56) scored normal range, 11.8% (n = 22) scored below the mean while 2.7% (n = 5) scored very poor. No significant difference on the PERF-FIT ladder run, ladder step, side jump, long jump and overhand throw (p = 0.26,0.16,0.54,0.90 and 0.99 respectively) and Alpha-fit longjump,4 x 10m SR, and 20mSR level (p = 0.99,0.77 and 0.10 respectively) between the group that met the WHO recommendation for PA and those who did not were found. However, there was a statistically significant difference between the two groups on BMI (p =0.05, with those not meeting the recommendation having a higher BMI). Significant correlations were observed between the PERF-FIT (power and agility) items and the Alpha-fit 4 x10m SR and Long jump. The Alpha-fit 4 x10m SR showed low to moderate correlation with the PERF-FIT ladder run, ladder step and long jump (rs= 0.26, 0.20, and 0.35 respectively) while the Alpha- fit long jump showed moderate to high correlations with the PERF-FIT side jump, long jump and overhand throw (rs= 0.36, 0.84 and 0.62 respectively). Conclusion Participants in the study demonstrated good muscular strength and agility measured by the long jump and 4 x10m SR as a result of habitual PA. However, the low participation in organized sports observed by this study could have accounted for the poor aerobic fitness demonstrated by low scores on the 20mSRT. The majority of the children were physically active and met global (WHO) recommendations for PA as reported by their parents. They mostly employed active transportation to get in and out of school (walking). Nevertheless, the BMI of the group of children not meeting the WHO recommendations was significantly higher than the group that met the recommendations. Scores on both Alpha-fit and PERF-FIT were however not significantly different between the two groups. The relation between PERF-FIT and Alpha-fit was mainly (80%) of the hypothesised magnitude. Majority the PERF-FIT (power and agility) items showed moderate to high correlation with the Alpha-fit 4 x10m SR and long jump which shows that the PERF-FIT measures a partly comparable construct to these tests. Identifying deficits in physical fitness in children living in low socioeconomic settings is recommended as a critical step toward the development of a large-scale effective prevention and/or intervention for children with low levels of physical fitness. Participants understood all the PERF-FIT instructions and carried out tests accordingly, testing was time-efficient since participants could be tested in small groups. Assessors found it easy to score participants. Our study findings show that the PERF-FIT performed well in this setting and may be used to assess fitness levels of children in this context.